2021
DOI: 10.1093/ndt/gfab292
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum globulin with all-cause mortality in incident hemodialysis patients

Abstract: Background Serum globulin is a major component of total protein and can be elevated in inflammatory disease states. While inflammation is common in hemodialysis patients and associated with mortality and morbidity, the association between serum globulin and mortality have never been examined in hemodialysis patients. Methods In a retrospective cohort of 104,164 incident hemodialysis patients treated by a large dialysis organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Furthermore, an in vitro experiment described albumin added to the albumin dialysis reduced the measurable amount of proinflammatory cytokine levels of IL-6, indicating albumin may also be an anti-inflammatory factor ( 21 ). Serum globulin, a classic inflammatory factor, increases during the inflammatory process ( 22 ). Inflammation typically causes an increase in the leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an in vitro experiment described albumin added to the albumin dialysis reduced the measurable amount of proinflammatory cytokine levels of IL-6, indicating albumin may also be an anti-inflammatory factor ( 21 ). Serum globulin, a classic inflammatory factor, increases during the inflammatory process ( 22 ). Inflammation typically causes an increase in the leukocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In the stage of sepsis, albumin can indirectly contribute to immunity by providing nitrogen for globulin production, resulting in hypoalbuminemia and elevated globulin concentration [44]. Pai et al indicated that higher serum globulin (≥ 38 g/L) contributed to a higher infection-related mortality risk in 104,154 incident hemodialysis patients [45]. Thus, a lower AGR can result from a combination of low albumin and high globulin, and the combined biomarker might be a robust predictor of S-AKI in elderly sepsis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In general, serum albumin is used to identify nutritional status, while serum globulin is used to assess the severity of chronic inflammation. As most biochemical markers, albumin, globulin, and albumin/globulin ratio levels are affected by several factors, such as fluid status [35][36][37] inflammatory acute changes, and nutritional status [15,[38][39][40][41]. Kaizu et al also demonstrated that muscle area was directly associated with serum albumin [42].…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not demonstrate an association between physical activity levels and globulin. Despite no previous study have investigated this association, a recent cohort study found that high globulin levels were associated with mortality in CKD patients, a phenomenon that can be explained by conditions associated with inflammation (e.g., infections, malignancies, hematological disorders of connective tissue diseases, and increased immunoglobulin fraction) [15,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation